Management of Common Goods: an Investigation at Parque Nacional da Serra da Canastra (PNSC), Minas Gerais (Management and Connections Journal, 2023)
The objective is to analyze the possibilities and alternatives for the effectiveness of a collective and cooperative management at Parque Nacional da Serra da Canastra (PNSC). The theoretical framework elucidates the concept of common goods. The research is qualitative and descriptive in nature. Data were collected through documentary research, non-participant observation and interviews. The analysis was based on the principles of good governance of common goods. The results point to many challenges for collective management. However, we found that in the period from 2018 to 2020 there was a greater interaction between the several players that integrate the park management, making it possible a more participatory discussion of the issues and building a more shared management process. The cooperative management of common goods is a possibility to develop a solid performance in the management of conflicts, given the diversity of relationships between the different players in the Park – a place that houses an array of common goods.